Criterion-referenced test of 20-meter multi-stage running test for the age group (13 to 16 year) in the Kingdom of Bahrain - Abdul Mahdi Ali Ahmed (sports creativity, 2025)
The purpose of this study was to reach a criterion-referenced test for 20 meter multi running test for the age group (13 to 16 years) in the Kingdom of Bahrain. The test used stopping points to categorize weight mass index. The researcher used descriptive survey method on a sample of (1631) that their ages verified from 13 to 16 years. He used the following body measurements (height, weight, and BMI and heart fitness measurement of 20 meter running). The data was analyzed using mean, standard deviation, flattening, torsion -coefficient-Test, percentage, kappa coefficient and Receiver Operating Characteristic curve (ROC). The findings showed that the rates of compatibility in the classification of children into fit and unfit in 20-meter running test, were very high with fitnessgram pacer test. Also, the area below the curve obtained from the measured level was acceptable at the point of incidence of obesity. However, the area below the curve from the measured level at the point of position to gain weight was weak.